Le pont Jacques-Cartier - Giroux, Éric (Histoire Québec, 2010)
Keywords: Ponts

Montréal, une île, des ponts - Conciatori, Christine (Continuité, 2002)
Keywords: Ponts

Il sera beau, impressionnant, mais jamais construit!: Le pont Royal-Albert - Fougères, Dany (Cap-aux-Diamants, 2019)
Keywords: Ponts

Le pont tubulaire et ferroviaire Victoria - Pratt, Michel (Histoire Québec, 2010)
Keywords: Chemins de fer; Ponts; Victoria (pont)

Le pont-tunnel Louis-Hippolyte-La-Fontaine. Une oeuvre moderne sur les traces du passé - Atelier d'histoire de la Longue-Pointe; Charbonneau, Réjean; Dugas, Philippe; Foisy, Marie-Hélène; Laferrière, Monique; Marien, Chantal (Atelier d'histoire Mercier-Hochelaga-Maisonneuve, 2007)
Keywords: Ponts; Tunnels

Vue sur le pont, quartier Sainte-Marie - Giroux, Éric (Ville de Montréal et Écomusée du fier monde, 2005)
Keywords: Ponts; Quartiers; Sainte-Marie

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels

Deux ponts à ne pas confondre: Honoré-Mercier et Saint-Laurent - Gravel, Denis (Histoire Québec, 2010)
Keywords: Canadien Pacifique; Chemins de fer; Ponts

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies

Le pont Royal-Albert, 1875-1876: histoire d'une bérézina sur fond de rivalités ferroviaires - Fougères, Dany (Revue d'histoire de l'Amérique française, 2022)
Keywords: Chemins de fer; Grand Tronc; Ponts

Paradoxe patrimonial: le pont-tunnel Louis-Hippolyte-La Fontaine et le village de Longue-Pointe - Cayouette-Ashby, Eve-Lyne (Bulletin de l'Association québécoise pour le patrimoine industriel, 2007)
Keywords: Longue-Pointe; Ponts; Saint-François-d'Assise (paroisse)

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

When Bridges Become Barriers; Montreal and Kahnawake Mohawk Territory - Rueck, Daniel (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Autochtones; Ponts

Le chemin de fer sur la glace - Lefort, Pierre (Histoire Québec, 2000)
Keywords: Canadien Pacifique; Chemins de fer; Longueuil; Ponts; Victoria (pont)

Retrouver les lieux de passages - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Ponts; Rivière des Prairies; Sault-au-Récollet

Transportons-nous, jadis! Une petite histoire du transport (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
Keywords: Automobile; Lachine (canal); Navigation; Ponts; Tramways; Transport en commun

Une île sans partage: la domination de Montréal à l'ère d'une nouvelle dynamique insulaire - Fougères, Dany; Shaffer, Valérie (Histoire de Montréal et de sa région, 2012)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal

An Undivided Island: Domination at the Dawn of a New Era - Fougères, Dany; Shaffer, Valérie (Montreal: The History of A North American City, 2018)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal